Characterization of the Temporal Pattern of Blood Protein Digestion in Rhodnius prolixus: First Description of Early and Late Gut Cathepsins - Henriques, Bianca Santos; Gomes, Bruno; Oliveira, Pedro Lagerblad; Garcia, Elói de Souza; Azambuja, Patrícia; Genta, Fernando Ariel (Frontiers in Physiology, 2021)
Rhodnius prolixus is one important vector for the parasite Trypanosoma cruzi in Latin America, where Chagas disease is a significant health issue. Although R. prolixus is a model for investigations of vector-parasite interaction and transmission, not much has been done recently to further comprehend its protein digestion. In this work, gut proteolysis was characterized using new fluorogenic substrates, including optimum pH, inhibition profiles, tissue and temporal expression patterns. Each protease possessed a particular tissue prevalence and activity cycle after feeding. Cathepsin L had higher activity in the posterior midgut lumen, being characterized by a plateau of high activities during several days in the intermediate phase of digestion. Cathepsin D showed high activity levels in the tissue homogenates and in the luminal content of the posterior midgut, with a single peak five days after blood feeding. Aminopeptidases are highly associated with the midgut wall, where the highest activity is located. Assays with proteinaceous substrates as casein, hemoglobin, and serum albumin revealed different activity profiles, with some evidence of biphasic temporal proteolytic patterns. Cathepsin D genes are preferentially expressed in the anterior midgut, while cathepsin L genes are mainly located in the posterior portion of the midgut, with specific sets of genes being differentially expressed in the initial, intermediate, or late phases of blood digestion.